Nepeta azadkouhensis (Lamiaceae), a new alpine-subnival species from the Central Alborz of Iran - Saberamoli, Siroos; Balali, Gholam Reza; Asri, Younes; Afsharzadeh, Saeed (Phytotaxa, 2019)
Nepeta azadkouhensis (Lamiaceae), a new species from Mazandaran province in northern Iran is described and illustrated. This taxon is similar to N. natanzensis and N. monocephala with terminal capitate inflorescences, tubular and curved corolla tubes as well as tubular calyces glabrous inside. It differs from N. natanzensis in corollas pink-purple, bracts and bracteoles smaller, as well as calyx with shorter teeth and a regular throat. It differs from N. monocephala in tall stems, procumbent to ascending and leaves arranged all along the stem. The new species is found in the alpine-subnival zone on scree at an elevation of 3700 to 3800 m.